Stable Metallicity of Low Dimentional WCrC Derivatives: A First‐Principles Study. Issue 5 (25th March 2021) - Liu, Guogang; Chen, Tong; Xu, Liang; Dong, Xiansheng; Cen, Kangwei; Zhu, Yuyuan; Xu, Zhonghui; Xiao, Xianbo
Abstract: The rapid development of 2D material MXenes family brings new opportunities for the application and development of materials science. Here, the structural and electronic properties of WCrC monolayer and its nanoribbons, and the effects of add‐atom adsorption in combination with strain engineering are presented by using first‐principles calculation. The result reveals that pristine WCrC monolayer is always dynamically stable and exhibits metallicity. Within a certain coverage range, the metallic WCrC monolayer can be transformed into semi‐metallic WCrCO2 with dual narrow band gap by adsorbing O atoms, but adsorbed H and Cl atoms cannot change its metal behavior. Moreover, the spin‐splitting of WCrC monolayer is obvious, but when the compressive strain increases to 8%, the energy bands of WCrC monolayer achieve a singular behavior of spin degeneracy. However, neither compressive strain nor tensile strain changes the metallicity of WCrC monolayer. Meanwhile, WCrC nanoribbons with diverse boundaries configurations and edge‐terminated atoms are all metallic, which indicates that boundary configurations and edge‐terminated atoms are not the key factors affecting the metallicity of WCrC nanoribbons. These results suggest that WCrC derivatives are mainly metallic materials, which are expected to be applied in the field of spintronics and may provide new opportunities for the development of metal ion battery electrodes. Abstract : The electronic structure of WCrC monolayer and its nanoribbons are metallic except for the semiconductive O adsorpted WCrC monolayer. Moreover, the WCrC monolayer can change from spin‐splitting to spin degeneracy by increases compressive strain to 8%. However, neither compressive strain nor tensile strain can change the metallicity of WCrC monolayer.